Epidemilogic survey of dermatophytosis in dogs and cats attended at the dermatology service of the College of Veterinary Medicine and Animal Science of UNESP - Botucatu - Palumbo, Mariana Isa Poci [UNESP]; De Araújo MacHado, Luiz Henrique [UNESP]; Paes, Antonio Carlos; Mangia, Simone Henriques [UNESP]; Motta, Rodrigo Gracia [UNESP] (Universidade Estadual de Londrina, 2010)
The objective of this study was to assess the medical records of the patients whose mycological culture of the hair in Sabouraud Dextrose Agar supplemented with chloramphenicol and cycloheximide was positive for dermathophytes, and review the cases of dermatophytosis. One hundred and thirty six medical records of patients (114 dogs and 22 cats) with dermatophytosis attended in a period of 54 months in the Veterinary Hospital of the UNESP - Botucatu were evaluated. Results obtained in this analysis have shown that the majority of the cultures were positive for Mycrosporum canis. There was no statistical difference between genders, but the number of defined breed dogs presenting dermatophytosis was higher than mongrel dogs. Among feline cases, however, there were a higher number of mongrel cats. The majority of the people and animals in contact with the patients did not report skin lesions. 32,5% 0f the dogs presented middle intensity itchiness, while in cats itchiness was absent in 77,3% of cases. 69,3% of the animals did not present clinical signs other than dermatological. Mean ages were 4 years in dogs and 3 years in cats. There was no statistical effect of season in the occurrence of dermatophytosis. Among animals submitted to Wood lamp evaluation, 40,9% of the dogs and 33,3% of the cats were positive for dermatophytes. Most dogs had generalized lesions, while the majority of cats presented focal lesions. The most common lesions observed were: alopecia, crusts and erythema.
Estudo epidemiológico das dermatofitoses em cães e gatos atendidos no serviço de dermatologia da Faculdade de Medicina Veterinária e Zootecnia da UNESP - Botucatu
Keywords: Cats; Dermatophytosis; Dogs; Epidemiology; Microsporum sp.; Trichophyton sp.